Teach for India : marketing an idea - Hennessy, Julie, (SAGE knowledge. Cases., 2016)
In 2008, Shaheen Mistri, founder of the nonprofit Teach For India (TFI), was grappling with applying and adapting the business and recruitment models of the successful U.S.-based Teach For America and UK-based Teach First to meet the challenges of the education sector in India. The case provides a review of the U.S.- and UK-based models, as well as an analysis of the factors that drove their growth in their respective markets.